Exploring sensitivity of mathematical model for the system of voltage symmetrization - Gnilitsky, Vitaliy; Polishchuk, Alexander; Petrosyan, Ruslan (Eastern-European Journal of Enterprise Technologies, 2016)
Contemporary control systems of symmetrization devices widely use microprocessor devices, the algorithms of work of which are based on mathematical models of voltage symmetrization. Moreover, important elements of control systems of such systems are the sensors of electrical magnitudes on whose error the error of calculation of parameters of symmetrization devices depends. For a correct choice of sensors of electric magnitudes, it is necessary to solve the inverse problem of sensitivity of mathematical model of the appropriate control systems. Therefore, the development of methods that study sensitivity of mathematical models of symmetrization devices control systems is a rather relevant task for electric power industry. We examined existing methods of determining sensitivity of mathematical models. The algorithm for solving the inverse problem of sensitivity for mathematical models, presented in the form of a “black box”, is proposed. It is revealed that the error in accuracy of sensors of electric magnitudes, which are necessary for practical implementation of the system of voltage symmetrization based on the examined model, must not exceed 0.5 %. Contemporary sensors of electric magnitudes and network analyzers, the measurement errors of which for the real values of voltages and currents do not exceed 0.2 %, for the shift angles between phase voltages and coefficients of powers do not exceed 0.5 %, are fully applicable for the development of such a system of voltage symmetrization. The resulting algorithm may be used when studying other mathematical models of the voltages and currents symmetrization systems, represented in the form of a “black box”. Results of such research might be applied to assess the accuracy of sensors of electric magnitudes of the voltages and currents symmetrization systems, the mathematical models of which are examined. This work is the result of continuing research, part of which is described in other papers of authors.